Neuroprotective effects of Ganoderma lucidum polysaccharides against traumatic spinal cord injury in rats. Issue 11 (November 2015) - Gokce, Emre Cemal; Kahveci, Ramazan; Atanur, Osman Malik; Gürer, Bora; Aksoy, Nurkan; Gokce, Aysun; Sargon, Mustafa Fevzi; Cemil, Berker; Erdogan, Bulent; Kahveci, Ozan
Abstract: Introduction: Ganoderma lucidum ( G. lucidum ) is a mushroom belonging to the polyporaceae family of Basidiomycota and has widely been used as a traditional medicine for thousands of years. G. lucidum has never been studied in traumatic spinal cord injury. The aim of this study is to investigate whether G. lucidum polysaccharides (GLPS) can protect the spinal cord after experimental spinal cord injury. Materials and methods: Rats were randomized into five groups of eight animals each: control, sham, trauma, GLPS, and methylprednisolone. In the control group, no surgical intervention was performed. In the sham group, only a laminectomy was performed. In all the other groups, the spinal cord trauma model was created by the occlusion of the spinal cord with an aneurysm clip. In the spinal cord tissue, caspase-3 activity, tumour necrosis factor-alpha levels, myeloperoxidase activity, malondialdehyde levels, nitric oxide levels, and superoxide dismutase levels were analysed. Histopathological and ultrastructural evaluations were also performed. Neurological evaluation was performed using the Basso, Beattie, and Bresnahan locomotor scale and the inclined-plane test. Results: After traumatic spinal cord injury, increases in caspase-3 activity, tumour necrosis factor-alpha levels, myeloperoxidase activity, malondialdehyde levels, and nitric oxide levels were detected. After the administration of GLPS, decreases were observed in tissue caspase-3 activity, tumour necrosis factor-alpha levels, myeloperoxidase activity, malondialdehyde levels, and nitric oxide levels. Furthermore, GLPS treatment showed improved results in histopathological scores, ultrastructural scores, and functional tests. Conclusions: Biochemical, histopathological, and ultrastructural analyses and functional tests reveal that GLPS exhibits meaningful neuroprotective effects against spinal cord injury.